Discovery of novel 4-aryl-thieno[1, 4]diazepin-2-one derivatives targeting multiple protein kinases as anticancer agents. Issue 8 (1st May 2018) - Lee, Junghun; Jung, Hoyong; Kim, Minjung; Lee, Eunkyu; Im, Daseul; Aman, Waqar; Hah, Jung-Mi
Graphical abstract: Abstract: A series of 4-aryl-thieno[1, 4]diazepin-2-one were synthesized and evaluated for their antiproliferative activities against the A375P melanoma and U937 hematopoietic cell lines. Several compounds showed very potent antiproliferative activities toward both cell lines and the activities were better than that of sorafenib, the reference standard. Derivatives were made as amide (8a –8i, 9a –9m ) and urea (10a –10d, 11a –11d ) with diverse hydrophobic moieties. One of the most potent inhibitor 10d, 1-(4-((4-ethylpiperazin-1-yl)methyl)-3-(trifluoromethyl)phenyl)-3-(4-(2-oxo-2, 3-dihydro- 1H -thieno [3, 4- b ][1, 4]diazepin-4-yl)phenyl)urea was found to be very potent inhibitor of multi-protein kinases including FMS kinase (IC50 = 3.73 nM) and is a promising candidate for further development in therapeutics for cancer.